Quakers living in the lion's mouth : the Society of Friends in Northern Virginia, 1730-1865 - Crothers, A. Glenn (Gainesville : University Press of Florida, 2012)
This examination of a Quaker community in northern Virginia, between its first settlement in 1730 and the end of the Civil War, explores how an antislavery, pacifist, and equalitarian religious minority maintained its ideals and campaigned for social justice in a society that violated those values on a daily basis. By tracing the evolution of white Virginians' attitudes toward the Quaker community, Glenn Crothers exposes the increasing hostility Quakers faced as the sectional crisis deepened, revealing how a border region like northern Virginia looked increasingly to the Deep South for its cult.
7. A "nest of abolitionists": antislavery goals and southern identities8. "The union forever": Northern Virginia quakers in the Civil War; Epilogue: conflicting paths of virtue in Nineteenth-Century America; Notes; Bibliography; Index.
Print version record.
Includes bibliographical references and index.
Master record variable field(s) change: 072
Keywords: Quakers -- Virginia, Northern -- History -- 18th century; Quakers -- Virginia, Northern -- History -- 19th century; Society of Friends -- Virginia, Northern -- History; Dissenters -- Virginia, Northern -- History; Pacifism -- Virginia, Northern -- History; Antislavery movements -- Virginia, Northern -- History; Quaker women -- Virginia, Northern -- History; Religious pluralism -- Virginia, Northern -- History; Whites -- Virginia, Northern -- Attitudes -- History; Virginia, Northern -- Social conditions; RELIGION -- Christianity -- Quaker; Antislavery movements; Dissenters; Pacifism; Quaker women; Quakers; Religious pluralism; Social conditions; Society of Friends; Whites -- Attitudes; Northern Virginia; RELIGION / Christianity / Quaker; 1700-1899; Electronic books; History